The Molecular Aspect of Antitumor Effects of Protease Inhibitor Nafamostat Mesylate and Its Role in Potential Clinical Applications - Chen, Xi; Xu, Zhijie; Zeng, Shuangshuang; Wang, Xiang; Liu, Wanli; Qian, Long; Wei, Jie; Yang, Xue; Shen, Qiuying; Gong, Zhicheng; Yan, Yuanliang (Frontiers in Oncology, 2019)
Nafamostat mesylate (NM), a synthetic serine protease inhibitor first placed on the market by Japan Tobacco in 1986, has been approved to treat inflammatory-related diseases, such as pancreatitis. Recently, an increasing number of studies have highlighted the promising effects of NM in inhibiting cancer progression. Alone or in combination treatments, studies have shown that NM attenuates various malignant tumors, including pancreatic, colorectal, gastric, gallbladder and hepatocellular cancers. In this review, based on several activating pathways, including the canonical NF-κB signaling pathway, TNFR1-related signaling pathway, and tumorigenesis-related tryptase secreted by mast cells, we summarize the anticancer properties of NM in existing studies both in vitro and in vivo. In addition, the efficacy and side effects of NM in cancer patients are summarized in detail. To further clarify NM’s antitumor activities, clinical trials devoted to validating the clinical applications and underlying mechanisms are needed in the future.